1985
DOI: 10.1002/jlb.37.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Enhance the Human Pokeweed Mitogen Lymphocyte Response

Abstract: The effect of endothelial cells (EC) on lymphocyte mitogen responses was examined. Irradiated or mitomycin C treated EC were co-cultured with allogeneic peripheral blood mononuclear cells (PBM), and proliferative responses to pokeweed mitogen (PWM) and phytohemagglutinin (PHA) were assessed by 3H-thymidine incorporation. Compared to lymphocyte responses in the absence of EC, EC co-culture enhanced PWM responses at 72 hours by 55 +/- 28%, 103 +/- 24%, and 96 +/- 9% at EC:PBM ratios of 1:30, 1:10, and 1:3, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, Shanahan et al [11] reported that virgin EC but not fibroblasts enhance the human lymphocyte response to PWM. Roska et al [19], utiliz ing guinea pig aortic EC which do not bear la anti gen, demonstrated that EC are capable of functioning as accessory cells for mitogen (phytohemagglutinin and concanavalin A)-induced T cell proliferation but are unable to present an antigen to primed T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Shanahan et al [11] reported that virgin EC but not fibroblasts enhance the human lymphocyte response to PWM. Roska et al [19], utiliz ing guinea pig aortic EC which do not bear la anti gen, demonstrated that EC are capable of functioning as accessory cells for mitogen (phytohemagglutinin and concanavalin A)-induced T cell proliferation but are unable to present an antigen to primed T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes and monocytes which are major participants in the immune response emigrate into tis sue through EC from blood vessels. It has been shown that human vascular EC were effective accessory cells for the proliferating response of mitogen-stimulated T lymphocytes [10,11] and were capable of presenting antigen to syngeneic T lymphocytes [12][13][14], In addi tion, it has been demonstrated that class II antigen ex pression by EC is inducible in vitro [ 15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented the adherence of T cells to EC (1], and the modulation by EC of T-lymphocyte proliferation in response to mitogens [2][3][4], and in mixed lymphocyte cultures [5], EC can also present antigen to T cells [6,7], We recently demonstrated that EC support mitogeninduced interleukin-2 (IL-2) secretion by T cells more efficiently than do equal numbers of mono cytes [8,9].…”
Section: Introductionmentioning
confidence: 99%